MAIN ASPECTS OF DELIVERY IN WOMEN AFTER CAESAREAN SECTION - Аmonova Madina Furkatovna , Nomozov Poyonbek Qarshiboyevich (Journal of Science in Medicine and Life, 2024)
According to many obstetricians and gynecologists, there is a concept that after a cesarean section, it is necessary to perform another cesarean section. However, recently, especially in foreign countries, as a result of advances in medicine and operative techniques, the postoperative period, the tactics of conservative management of women with scars on the uterus are increasing. According to the literature [2,6], 60-80% of women, i.e. 3-4 out of every 5 women who underwent a first-time cesarean section, can give birth through natural childbirth. The frequency of caesarean section is the main reason for the increase in the number of women with a uterine scar. The choice of tactics of pregnancy, the optimal timing and methods of delivery in such patients presents considerable difficulties in each specific case and should be addressed individually.